FAMOUS SHRINES (Multidisciplinary Journal of Science and Technology, 2025)
This article provides information about the famous shrines, ancient shrines and tombs located in the territory of the Beruni district of the Republic of Karakalpakstan, their history, as well as the myths and legends related to them.